Stabilizing Thermoelectric Figure‐of‐Merit of Superionic Conductor Cu2Se through W Nanoinclusions. Issue 7 (29th April 2020) - Bohra, Anil Kumar; Bhatt, Ranu; Singh, Ajay; Bhattacharya, Shovit; Basu, Ranita; Bhatt, Pramod; Navaneethan, Mani; Sarkar, Shaibal K.; Anwar, Shahid; Muthe, Kunal Puranchand; Aswal, Dinesh Kumar
Abstract : Cu2 Se exhibits a high figure‐of‐merit ( ZT ) >1 due to the scattering of phonons by mobile Cu + ions, but migration of the Cu + ions leads to chemical instability at high temperature. It is demonstrated that the incorporation of W in the Cu2 Se matrix results in peak ZT of 2.1 ( ZT avg  = 0.93) at 878 K. After the first thermal cycle, the peak ZT of the composite decreases to stable value of ≈1.5 ( ZT avg  = 0.97). The enhanced stability of the nanocomposite along with high ZT avg is attributed to the covering of Cu2 Se grain boundaries with W that inhibits Cu + migration, reduces Se loss, and improves charge carrier mobility. Abstract : The incorporation of W in Cu2 Se results in peak ZT of 2.1 ( ZT avg  = 0.93) at 878 K, which decreases to a stable value of ≈1.5 ( ZT avg  = 0.97) after the first thermal cycle. The improved stability is attributed to the presence of W at Cu2 Se grain boundaries that reduces Se loss as well as inhibits Cu + migration.